2015
DOI: 10.1089/mdr.2014.0108
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression Levels of Chromosomal AmpC β-Lactamase in ClinicalEscherichia coliIsolates and Their Effect on Susceptibility to Extended-Spectrum Cephalosporins

Abstract: Forty-nine clinical Escherichia coli isolates, both extended-spectrum β-lactamase (ESBL) negative and ESBL positive, were studied to investigate whether increased AmpC expression is a mechanism involved in cefoxitin resistance and if this influences the third-generation cephalosporin activity. Nine of 33 (27.2%) cefoxitin-resistant (minimum inhibitory concentration [MIC] >8 mg/L) isolates showed hyperproduction of chromosomal AmpC (c-AmpC) based on (1) at least two positive tests using AmpC inhibitors, (2) mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Our study demonstrated that mutation at position −32 increased AmpC expression by 5.98 folds based on RT–qPCR assay. Similarly, mutations at positions −11, −20, −21, −42, −1 and +58 cause increased AmpC expression in the range of 1.39 to 13.87 folds, which is in agreement with the previously reported studies 3739 . Hyper-production of AmpC leads to increased resistance to cephalosporins as corroborated in our DEC isolates.…”
Section: Discussionsupporting
confidence: 93%
“…Our study demonstrated that mutation at position −32 increased AmpC expression by 5.98 folds based on RT–qPCR assay. Similarly, mutations at positions −11, −20, −21, −42, −1 and +58 cause increased AmpC expression in the range of 1.39 to 13.87 folds, which is in agreement with the previously reported studies 3739 . Hyper-production of AmpC leads to increased resistance to cephalosporins as corroborated in our DEC isolates.…”
Section: Discussionsupporting
confidence: 93%
“…This may also have been the cause of the greater variability in CFU counts at levels around the static dose level than at other levels of exposure. Another explanation could be that there were diverse levels of transcription of beta-lactamases, given the differential levels of expression of beta-lactamase enzymes in bacteria (19,20), and the presence of various beta-lactamase variants may indicate the reason for the differential C T s of tazobactam (16).…”
Section: Discussionmentioning
confidence: 99%
“…Colistin resistance has been associated with mutations in the genes coding for the PmrAB two-component regulatory system that regulates the addition of aminoarabinose to lipid A [207]. Additionally, mutations resulting in increased production of β-lactamases, e.g., by mutations in the promoter of the chromosomal ampC gene [208] or by increase of plasmid copy number [150] have been described, among others. In addition, the genes have evolved over the years, showing a large number of β-lactamase variants with point mutations in the gene resulting in changes in the amino-acid sequence [209].…”
Section: Mutation and Biofilmsmentioning
confidence: 99%